Staging as Communicative Activity of Shared Experiences a Way into a Fellowship for Deaf Children with Autism - Janne Madsen; Bjørk Kehlet (MDPI AG, 2023)
We explore whether staging (a combination of symbols, drawings, paintings, and re-creating action using Playmobil figures) used as a communicative activity of shared experiences influences the sense of fellowship. This study is part of a combined research and development project, and the findings are canalised back into the daily work. The assistants are interviewed, and the data are analysed in a coding process. We found that (1) 'being confident' is important for belongingness. Staging supports a shared understanding and a shared feeling of belonging. We also found that (2) developing a shared repertoire of concepts is possible when staging, and this scaffolds the fellowship. However, the concepts and the communication must (3) be meaningful to all parties. One does not take part in communication without meaning, and when one does not participate, one is not part of the fellowship. Staging enabled Magne, the main person in this study, to express himself better. Moreover, when discussing a shared experience with the personal assistants, Magne seemed to communicate well and showed signs of belonging. We conclude that communication about shared activities and experiences leads to interest and engagement and fosters a shared feeling of 'doing something together' and being part of a fellowship.